Building Information Modelling in Structural Engineering: A Qualitative Literature Review - Vittoria Ciotta; Domenico Asprone; Gaetano Manfredi; Edoardo Cosenza (CivilEng, 2021)
Over the past decade, the fields of civil engineering, i.e., structural engineering, have increasingly used the building information modelling (BIM) approach in both professional practice and as the focus of research. However, the field of structural engineering, which can be seen as a sub-discipline of civil engineering, misses, as far as the authors are aware, a real state-of-the-art on the use of BIM in this regard. The aim of this paper, therefore, is to start bridging that gap. In particular, the authors have conducted a traditional literature review on the utilisation of BIM in structural engineering, enabling them to perform a detailed content analysis of publications. The qualitative investigation of the literature that the authors have conducted has highlighted six main BIM uses in structural engineering: (1) structural analyses; (2) production of shop drawings; (3) optimized structural design, early identification of constructability issues, and a comparison of different structural solutions; (4) seismic risk assessments; (5) existing-condition modelling and retrofitting of structures; and (6) structural health monitoring. Each of these is discussed in relation to their reference workflows; use of information models; information exchanges; and main limitations. In the conclusions, the authors identify current gaps in knowledge, as well as likely developments and improvements in the utilization of BIM in structural engineering. The authors also outline the possible significance of this work more broadly.